Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1447-0756.1990.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐Meigs' Syndrome Secondary to Broad Ligament Leiomyoma: A Case Report

Abstract: An unusual and rare case of broad ligament leiomyoma with massive ascites and bilateral pleural effusion is described. The ascites and pleural effusion resolved dramatically following removal of the tumor. Patients with pseudo‐Meigs' syndrome may present a diagnostic problem as they masquerade as carcinoma with malignant effusions. Thus they should always be considered for exploratory laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…They are mostly from gastro-intestinal (colo-rectal and gastric) cancers [4] but also from breast [5], renal cancers [6] and peritoneal gliomatosis [7]. The syndrome has also been reported in a few cases of leiomyomas of the uterus [8] and of the broad ligament [9].…”
Section: Discussionmentioning
confidence: 99%
“…They are mostly from gastro-intestinal (colo-rectal and gastric) cancers [4] but also from breast [5], renal cancers [6] and peritoneal gliomatosis [7]. The syndrome has also been reported in a few cases of leiomyomas of the uterus [8] and of the broad ligament [9].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly reported presenting signs are abdominal distention and 'fullness', dyspnoea, and a palpable abdominal mass. In one case with a GCT, vaginal bleeding (an oestrogen associated clinical sign) was also present (Rush 1976;O'Flanagan et al 1987;Buckshee et al 1990;Choi et al 2005;Kurai et al 2005;Maeda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is an important consideration in the differential diagnosis of ovarian cancer, and rarely causes fatal manifestations . Only 32 studies on pseudo‐Meigs' syndrome complicated with uterine leiomyoma have been reported using a medline search (search terms: pseudo‐Meigs' and leiomyoma, leiomyoma and ascites) since 1900 (Table ) . The association of uterine leiomyoma with ascites and/or PE was first reviewed by Kelly and Cullen in 1909 .…”
Section: Discussionmentioning
confidence: 99%